Frontiers of fundamental and computational physics : 9th international symposium, Udine and Trieste, Italy, 7-9 January 2008 - International Symposium on Frontiers of Fundamental Physics (9th : 2008 : Udine and Trieste, Italy); Sidharth, B. G. (Burra Gautam), 1948- (Melville N.Y. : American Institute of Physics, 2008)
Includes bibliographical references and author index.